Western Sahara and the United States: Clientelism and exceptionalism in Africa’s last colony - Smith, Jeffrey J. (Africana Studia, 2020)
This paper assesses the historical and political connection of the United States to what the United Nations calls the “question” of Western Sahara. The analysis begins with the American approach to decolonization and the historical circumstances of the Spanish Sahara. America’s relationship with the principal states involved is examined together with its reluctance to engage the Saharawi national liberation movement, the Polisario Front. The contemporary periods of United States involvement in Western Sahara, as the territory was styled after 1975, are identified. De-classified US diplomatic telegrams for the era until 1980 and leaked telegrams for the years 2003 to 2010 are considered. The nature and prospect of continuing US involvement is discussed. Keywords: decolonization, diplomacy, United States, Western Sahara.